«To call fools into a circle»: Benjamin’s interpretation of As you like it and The Tempest (Itinera, 2019)
Calderon and Shakespeare are the two main authors that lie behind Benjamin’s examination of the German baroque drama. This paper addresses the importance of Shakespeare in his difference from the other big European cousin, Calderon. This does not mean that, according to Benjamin, Shakespeare is more important than Calderon (his beautiful essay on Calderon of 1923 contradicts this point), but rather that the English author brings to light an element that in Calderon is in some way missing. This is what Benjamin in some critical texts from the period of the Trauerpielbuch calls the «dramatic».Why does Benjamin say here that the dramatic precedes the tragic? And what does this have to do with the two Shakespearian characters he refers to in a letter of the same year, Caliban and Ariel? Moreover, is the interpretation of The Tempest that this passage implies the same as the one that he suggested in his previous essay on As you like it (1918)?These questions will lead to a few passages of the Trauerspielbuch that were particularly difficult to translate (not only in the two Italian previous translations, but also in the first English version, by John Osborne) and that can shed light on some important aspects of the book itself. In this context, another Shakespearian character will come to the aid, the Jacques of As you like it, with his Greek invocation «to call fools into a circle».